Critical illness polyneuromyopathy in septic patients: Is it possible to diagnose it in a bedside clinical examination? - Débora Schmidt; Ana Cláudia Coelho; Fernando Nataniel Vieira; Vitor Félix Torres; Augusto Savi; Silvia Regina Rios Vieira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To determine the sensitivity and specificity of peripheral and respiratory muscle strength tests in diagnosing critical illness polyneuromyopathy (CIPNM), compared with an electrophysiological examination. Methods: Fifty septic patients who required mechanical ventilation for at least five days, and without a previous history of muscle weakness, were included. Peripheral muscle strength was assessed using the Medical Research Council (MRC) score, handgrip strength by dynamometry, and respiratory muscle strength with maximum respiratory pressures. Diagnosis of CIPNM was either confirmed or rejected by an electrophysiological examination. Receiver operating characteristic curve analysis was performed to determine the cut-off values with the best sensitivity (SN) and specificity (SP) of the studied variables in the presence or absence of CIPNM. Results: Patients with CIPNM were older, more critical (APACHE IV/SAPS 3), had a longer hospitalization, required mechanical ventilation for longer, and had a higher rate of intensive care unit readmission. Cutoff values identified CIPNM patients using MRC scores, dynamometry according to sex, maximal expiratory and inspiratory pressures, as well as being confirmed by the electrophysiological examination, with good sensitivity and specificity: < 40 (SN: 0.893; SP: 0.955); < 7 kg (SN: 1; SP: 0.909) for men, < 4 kg (SN: 0.882; SP: 1) for women; < 34 cmH2O (SN: 0.808; SP: 0.909) and > −40 cmH2O (SN: 0.846; SP: 0.909), respectively. Conclusion: The MRC score, dynamometry or maximum respiratory pressures can be used to identify patients with CIPNM at the intensive care bedside assessment. The healthcare professional can choose any of the methods studied to evaluate the patient, based on his experience and the resource available.